Practical Implementation of Fair Trade and Social Welfare for Small Producers: Analysis of Mitra Bali Fair Trade Craftsmen - Dewa Ngakan Putu Abhi Mahardika; Putu Ratih Kumala Dewi (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
Mitra Bali Fair Trade is a business entity that collaborates with craftsmen to implement fair trade practices in the export of Balinese handicraft commodities. Despite the potential, the effectiveness of the entity is affected by craftsmen’s lack of understanding of fair trade. Therefore, this study aimed to discuss craftsmen’s understanding as small producers regarding fair trade principles as well as their benefits. The study procedures were conducted in Gianyar Regency among craftsmen working with Mitra Bali using a qualitative method and a phenomenological approach. Data collection was carried out through in-depth interviews with seven informants accompanied by relevant literature studies. The results showed that craftsmen understood the ten principles of fair trade, and the implementation of fair trade could bring social welfare to the participants. The results of this study aim to contribute to the academic discourse regarding fair trade and address the practical issue of its implementation in Bali.